Bioactive collagen-grafted poly-L-lactic acid nanofibrous membrane for cartilage tissue engineering - Chen, Jyh-Ping; Li, Sheng-Feng; Chiang, Yi-Ping (Journal of nanoscience and nanotechnology, 2010)
Biodegradable nanofibrous membrane was prepared from poly-L-lactic acid by electrospinning and used as a scaffold for cartilage tissue engineering. Operating parameters during the electrospinning process were studied in terms of their influences on fiber diameter, membrane porosity and pore size. In order to improve cell attachment and growth, nanofibrous membrane was subject to DC-pulsed oxygen plasma treatment, followed by acrylic acid grafting and collagen coating by covalent binding of collagen to carboxylic moieties of the polyacrylic acid. The membrane was fully characterized for its physical and chemical properties. Primary chondrocyte cells seeded into the membrane proliferated well and maintain high viability within the membrane from Confocal Laser Scanning Microscopy. Cell differentiation was confirmed by secretion of glycoaminoglycan and collagen during the cultivation period. Scanning electron microscope observation of the cell-scaffold construct confirms the tight attachment of cells to nanofibers and in-growth of cells into the interior of the membrane with proper maintenance of morphology and structure of chondrocytes.